Cyclone wind threat estimates for the Bay of Bengal - JARRELL, JERRY D. (MAUSAM, 1982)
Public officials are frequently required to make decisions relative to cyclone preparedness actions. For such decisions to be defensible they usually adhere to an official government forecast, yet some allowance for forecast error must be made. Complex relationships between errors in track and in the forecast wind distribution confused by lack of user familiarity makes this a particularly difficult problem. This paper introduces the concept of wind threat as a means of quantifying the risk thereby allowing simultaneously for all types of errors. Some simple examples of the use of such probabilities in decision making are presented and the model which makes the threat estimates is described.